2012
DOI: 10.1007/s11682-012-9159-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural integrity and postconcussion syndrome in mild traumatic brain injury patients

Abstract: The presence of a postconcussion syndrome (PCS) induces substantial socio-professional troubles in mild traumatic brain injury (mTBI) patients. Although the exact origin of these disorders is not known, they may be the consequence of diffuse axonal injury (DAI) impacting structural integrity. In the present study, we compared structural integrity at the subacute and late stages after mTBI and in case of PCS, using diffusion-weighted imaging (DWI). Fifty-three mTBI patients were investigated and compared with 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 46 publications
3
55
2
Order By: Relevance
“…More recent work by Messé and associates 65 reported that patients with poor outcome 3-4 months after mTBI demonstrated reductions in long association white matter tracts (assessed between 7-28 days postinjury) compared with those with good outcome. In addition, Messé and colleagues 66 reported that patients with mTBI and PCS symptoms demonstrated greater and more widespread loss of white matter integrity that did not resolve over 6 months postinjury as did that of patients with mTBI and PCS symptoms that had resolved. Future research with this cohort of patients will include the analysis of DTI to ascertain whether TAI detected through acute neuroimaging (e.g., < 96 h post-injury) is associated with concurrent neuropsychological performance and/or predictive of later outcome.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work by Messé and associates 65 reported that patients with poor outcome 3-4 months after mTBI demonstrated reductions in long association white matter tracts (assessed between 7-28 days postinjury) compared with those with good outcome. In addition, Messé and colleagues 66 reported that patients with mTBI and PCS symptoms demonstrated greater and more widespread loss of white matter integrity that did not resolve over 6 months postinjury as did that of patients with mTBI and PCS symptoms that had resolved. Future research with this cohort of patients will include the analysis of DTI to ascertain whether TAI detected through acute neuroimaging (e.g., < 96 h post-injury) is associated with concurrent neuropsychological performance and/or predictive of later outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in Table 1, the majority of studies published within the last 2 years employ tractbased spatial statistics (TBSS), which allow for the interrogation of multiple fiber tracts, and yield additional diffusion metrics including RD and MD. Several recently published studies show some consistency of results, demonstrating elevated RD and MD in concussion [21][22][23]25] and indicating that these measures could potentially better 'track' fiber tract damage compared to FA.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 79%
“…Although the number of published studies using DTI has more than quadrupled since 2002 [12], the utility of DTI for assessing white matter tract injury in concussion is still unclear. Several recent DTI studies have reported either high [13][14][15][16][17][18][19] or low [18,[20][21][22][23][24][25][26] FA following concussion, and one longitudinal study has shown both increases as well as decreases of anisotropy within the same individual over time [18] (see Table 1). These disparate findings in the recent concussion literature have spurred the hypothesis that anisotropic differences in concussed patients could differ depending on whether the patient is imaged immediately after the concussion or months/years postconcussion [13,14].…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that these kinds of injury result in a disconnection within and between brain areas that is manifested as a loss or reduction of cognitive function 14, 15, 16. Functional connectivity studies acquired in the functional magnetic resonance imaging (fMRI) using a resting state paradigm in patients with mTBI report abnormalities in brain networks that include visual processing, limbic, motor, and cognitive functions,17 default mode function,18 default mode regulation,19 and aberrant connectivity in thalamo‐cortical networks that correlated with neurocognitive function and clinical symptomatology 20…”
Section: Introductionmentioning
confidence: 99%